Congenital hyperinsulinism and Poland syndrome in association with 10p13–14 duplication. (31st March 2017) - Giri, Dinesh; Patil, Prashant; Hart, Rachel; Didi, Mohammed; Senniappan, Senthil
Summary: Poland syndrome (PS) is a rare congenital condition, affecting 1 in 30 000 live births worldwide, characterised by a unilateral absence of the sternal head of the pectoralis major and ipsilateral symbrachydactyly occasionally associated with abnormalities of musculoskeletal structures. A baby girl, born at 40 weeks' gestation with birth weight of 3.33 kg (−0.55 SDS) had typical phenotypical features of PS. She had recurrent hypoglycaemic episodes early in life requiring high concentration of glucose and glucagon infusion. The diagnosis of congenital hyperinsulinism (CHI) was biochemically confirmed by inappropriately high plasma concentrations of insulin and C-peptide and low plasma free fatty acids and β-hydroxyl butyrate concentrations during hypoglycaemia. Sequencing of ABCC8, KCNJ11 and HNF4A did not show any pathogenic mutation. Microarray analysis revealed a novel duplication in the short arm of chromosome 10 at 10p13–14 region. This is the first reported case of CHI in association with PS and 10p duplication. We hypothesise that the HK1 located on the chromosome 10 encoding hexokinase-1 is possibly linked to the pathophysiology of CHI. Learning points: Congenital hyperinsulinism (CHI) is known to be associated with various syndromes. This is the first reported association of CHI and Poland syndrome (PS) with duplication in 10p13–14. A potential underlying genetic link between 10p13–14 duplication, PS and CHI is a possibility.